2020
DOI: 10.1021/acs.est.9b06926
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption and Photocatalytic Degradation of Extracellular Antibiotic Resistance Genes by Molecularly-Imprinted Graphitic Carbon Nitride

Abstract: There is a growing need to mitigate the discharge of extracellular antibiotic resistance genes (ARGs) from municipal wastewater treatment systems. Here, molecularly-imprinted graphitic carbon nitride (MIP-C 3 N 4 ) nanosheets were synthesized for selective photocatalytic degradation of a plasmid-encoded ARG (bla NDM-1 , coding for multidrug resistance New Delhi metallo-β-lactamase-1) in secondary effluent. Molecular imprinting with guanine enhanced ARG adsorption, which improved the utilization of photogenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(25 citation statements)
references
References 63 publications
(102 reference statements)
0
25
0
Order By: Relevance
“…To solve this issue, there have been efforts to produce photocatalytic materials that show selectivity to the substrates. Coatings with selectively adsorbing materials [131] and molecular printing [132] increase the selectivity of photocatalysis for the removal of pollutants, while the adsorption of ions on TiO 2 has been used to increase its efficiency in CO 2 reduction and increase the formation of useful products like CH 4 [133].…”
Section: Effect Of Matricesmentioning
confidence: 99%
“…To solve this issue, there have been efforts to produce photocatalytic materials that show selectivity to the substrates. Coatings with selectively adsorbing materials [131] and molecular printing [132] increase the selectivity of photocatalysis for the removal of pollutants, while the adsorption of ions on TiO 2 has been used to increase its efficiency in CO 2 reduction and increase the formation of useful products like CH 4 [133].…”
Section: Effect Of Matricesmentioning
confidence: 99%
“…Interestingly, studies showed that use of adsorption-photocatalysis simultaneously grab attention for efficient removal of organic pollutant due to recombination of electron-hole pair disadvantage of photocatalysis (Yuan et al, 2020). Various studies showed significant removal of antibiotics using adsorption-photocatalysis treatment such as ciprofloxacin (with 59.5% adsorption and 82.5 % degradation in 60 min), tetracycline (with 18% adsorption and 70% degradation in 90 min), ofloxacin (with 93.4% adsorption and photocatalytic degradation in 30 min) (Chen et al, 2020).Motivated by previous studies, Barium ferrites with exceptional magnetic and photocatalytic property used for synthesis of new material in order to develop the dual functioning material by combining the advantages of both adsorption-photocatalysis technologies (Roonasi and Mazinani, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have removed fluoroquinolone antibiotic pollutants in the environment mainly involving advanced oxidation, adsorption, and photodegradation . Photocatalysis can use pollution-free and renewable solar energy to convert pollutants to nontoxic small molecules such as CO 2 and H 2 O. Ye’s team first reported Ag 3 PO 4 with prominent photocatalytic performance due to its strong electron–hole pairs (e – –h + ) separation effect.…”
Section: Introductionmentioning
confidence: 99%
“…4 Conventional sewage treatment technology for fluoroquinolone antibiotics is ineffective; thus, a technology to effectively remove fluoroquinolone antibiotic residues in aquatic environments is urgently needed to be developed. 5 In recent years, researchers have removed fluoroquinolone antibiotic pollutants in the environment mainly involving advanced oxidation, 6 adsorption, 7 and photodegradation. 8 Photocatalysis can use pollution-free and renewable solar energy to convert pollutants to nontoxic small molecules such as CO 2 and H 2 O. Ye's team 9 first reported Ag 3 PO 4 with prominent photocatalytic performance due to its strong electron−hole pairs (e − −h + ) separation effect.…”
Section: ■ Introductionmentioning
confidence: 99%